Changes of Body Mass Index and Lipid Profile in Injectable Depot Medroxyprogesterone Acetate and Levonorgestrel Implant Acceptors - Daido, Irwan (Indonesian Journal of Obstetrics and Gynecology, 2014)
Objective: To determine the comparison of body mass index (BMI) among acceptors of injectable depot medroxyprogesterone acetate (DMPA) with levonorgestrel implant acceptors for 1 year and comparison of lipid profiles between depot medroxyprogesterone acetate acceptors with levonorgestrel implants for 1 year. Method: This study was conducted at dr. Wahidin Sudirohusodo hospital, Makassar and its satellite hospitals as well as family planning social service cooperation between the National Family Planning Coordinating Board with the Department of Obstetrics and Gynecology Hasanuddin University. Result: The results showed the increase in BMI of levonorgestrel implant acceptors (1.25 kg/m2) was greater than DMPA acceptors (0.74 kg/m2). HDL cholesterol and triglycerides did not change significantly in either groups. LDL cholesterol was increased in DMPA acceptors (9.63 mg/dl) and decreased in implant acceptors (1.62 mg/dl). Total cholesterol increased in DMPA acceptors at 8.67 mg/dl) while in the levonorgestrel implant acceptors it was decreased by 5.37 mg/dl. Conclusion: Weight gain occured among acceptors of DMPA and implant however the weight gain is more profound among the implant acceptors. [Indones J Obstet Gynecol 2014; 3: 121-126] Keywords: body mass index, DMPA, levonorgestrel implant, lipid profile